Broadcasters Perception Of Television Programs: A Study On Al-Hijrah Islamic Malaysian Television Channel - Osama Kanaker; Zulkiple Abd Ghani (Universiti Sains Islam Malaysia, 2024)
This paper identifies four main characteristics of Islamic television programs. They are reality and objectivity, comprehensiveness, moderation and application of Islamic distinctive features. A questionnaire was distributed to the broadcasters of Al-Hijrah Television to determine their perception on the characteristics of applying the aforementioned characteristics to their programs. Programs of Al-Hijrah Television were also observed to further investigate the application of the characteristics to Al-Hijrah Television programs. The main finding of this paper is that despite the satisfaction of Al-Hijrah Television broadcasters, the application of the four characteristics to Islamic television programs does not suffice the need of the audience. It was also found out that drama programs are more effective than traditional programs in delivering the Islamic message despite the rarity of Islamic drama.